An estrogen receptor targeted ruthenium complex as a two-photon photodynamic therapy agent for breast cancer cells. Issue 51 (6th June 2018) - Zhao, Xueze; Li, Mingle; Sun, Wen; Fan, Jiangli; Du, Jianjun; Peng, Xiaojun
Abstract : In this study, we reported a tamoxifen modified Ru(ii ) polypyridyl complex (Ru-tmxf ) as an estrogen receptor (ER) targeted photosensitizer. Abstract : In this study, we reported a tamoxifen modified Ru(ii ) polypyridyl complex (Ru-tmxf ) as an estrogen receptor (ER) targeted photosensitizer.Ru-tmxf displays enhanced cellular uptake and PDT efficiency toward breast cancer cells with high ER expression due to the specific targeting of tamoxifen to ER and finally localizes in lysosomes. Moreover, Ru-tmxf can be activated by two-photon excitation, generating 1 O2 to damage lysosomes and result in cell death.